Kajian Analisis Pengendalian Tikus Sawah (Rattus argentiventer) pada Tanaman Padi - Harini, Nyang Vania Ayuningtyas; Ratna Suminar; Permadi, Choliq (AgriMalS, 2025)
Rice cultivation faces several challenges, including attacks by plant pests (OPT). The rice rat (Rattus argentiventer) is a pest that attacks rice plants, both in lowland and upland rice fields. Rice rats cause damage and losses of up to 80% both before and after harvest and negatively impact food security. The aim of this study was to determine the most effective method for controlling rice rats (Rattus argentiventer). The research method employed a qualitative approach, utilizing secondary data on rat populations and control methods in Indonesia from 2020 to 2024. Data analysis was descriptive and presented in tables and figures. The number of catches using the gropyokan method varies significantly depending on several factors, including area size, rat population levels, the number of farmers involved, and the duration of the gropyokan. This variation is demonstrated by the data. For example, there were 534 rats in a 50-hectare area in Batubara, and thousands (3,500) in Sragen could be reached within three hours of operation in some locations, and nearly 6,000 rats in others. Rat control using the rice-fish method improves land use efficiency and also helps control plant pests, particularly rice field rats. Rat control using the rice-fish method improves land use efficiency and also helps control plant pests, particularly rice field rats. Using rat traps is also an effective and environmentally friendly control method. Traps capture rats, both live and dead, without leaving chemicals in the environment. Controlling rats using fumigation is much safer than other methods of rodent control.